2020
DOI: 10.1016/j.sleep.2020.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Job-related factors associated with changes in sleep quality among healthcare workers screening for 2019 novel coronavirus infection: a longitudinal study

Abstract: Background Sleep disorders may exacerbate many physical and mental health conditions, causing difficulty function in a healthcare setting. Workers screening for the 2019 novel coronavirus (2019-nCoV) infection have a high risk of not only occupational exposure to the virus but also sleep disorders. However, the job-related factors associated with reduced sleep quality remain unclear. Methods All healthcare workers temporarily scheduled to screen the 2019-nCoV patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
64
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 18 publications
1
64
1
4
Order By: Relevance
“…The seven studies [ 43 , 51 , 55 , 64 , 75 , 76 , 123 ] with a longitudinal design showed satisfactory quality, meeting seven or more criteria. However, no study met all eleven criteria.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The seven studies [ 43 , 51 , 55 , 64 , 75 , 76 , 123 ] with a longitudinal design showed satisfactory quality, meeting seven or more criteria. However, no study met all eleven criteria.…”
Section: Resultsmentioning
confidence: 97%
“…Namely, 29 studies performed data collection in earlier phases of the outbreak in the respective country [64-66, 77, 79-81, 84-89, 91, 96, 98, 100, 103, 105, 106, 108, 109, 111-115, 120, 126], nine during the outbreak [69, 73, 82, 95, 97, 101, 110, 118, 125], 32 in later phases [41, 42, 44-46, 50, 53, 54, 56, 59-61, 67, 68, 70-72, 74, 78, 83, 90, 92-94, 102, 104, 107, 117, 119, 121, 122, 124], and eight after the end of the outbreak [47-49, 52, 57, 58, 63, 99]. Another seven studies focusing on SARS [43, 51, 55], MERS [64], and COVID-19 [75, 76, 123] also included follow-up data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-one studies reported on fear related to an infectious disease outbreak [ 29 – 31 , 35 37 , 43 , 46 , 53 , 55 , 61 , 64 , 72 , 74 , 78 83 , 85 – 87 , 94 , 95 , 99 , 100 , 107 – 109 , 115 , 117 , 119 , 123 , 128 , 131 , 132 , 134 , 142 , 146 , 147 , 155 – 173 ]. Most of the studies ( n = 52) reported physician’s fear of infecting themselves or their family.…”
Section: Resultsmentioning
confidence: 99%
“…Physicians reported the importance of having social support from friends, family, colleagues, and professionals (e.g., counsellors) in 29 studies [ 28 , 30 , 39 , 43 , 44 , 48 , 56 , 58 , 67 , 72 , 78 , 83 , 91 , 99 , 102 , 106 , 115 , 119 , 131 , 150 , 155 , 163 , 172 , 192 , 202 – 205 ]. Several studies ( n = 29) described positive personal coping strategies such as maintaining a positive attitude and resilience [ 37 , 46 , 83 , 100 , 106 , 108 , 136 , 202 , 205 , 206 ], practicing self-care (e.g., physical activity, eating well, resting, engaging in activities they enjoy) [ 30 , 35 , 56 , 65 , 70 , 91 , 102 , 103 , 117 , 119 , 129 , 131 , 150 , 151 , 207 ], and engaging with religious practices [ 39 , 46 , 131 , 205 ] as a way to mitigate negative psychological outcomes. In contrast, two studies reported that physicians engaged in avoidance coping strategies (e.g., screaming, crying, denial, self-blame, disengaging, substance abuse, etc.)…”
Section: Resultsmentioning
confidence: 99%